Pemecahan Masalah dalam Menyelesaikan Soal Jumping Task ditinjau dari Gaya Kognitif - Hobri Hobri; Dianita Tussolikha; Ervin Oktavianingtyas (Jurnal Elemen, 2020)
The provision of jumping tasks (JT) is an effort to improve students' problem-solving abilities. Descriptive qualitative research was conducted to describe and analyze students' ability to solve mathematical problems, both in the field-dependent cognitive style (FD) and independent field (FI). JT is a high-level question, C4-C6, in Bloom's taxonomy on the Three Variable Linear Equation System topic. The subjects in this study were students of class X MIPA 1 of SMA Negeri 4 Jember with 30 students consisting of 5 FD students and 25 FI students. The data collection method uses tests (JT questions) and interviews. The results showed the differences in FD and FI subjects' ability in the stages of carrying out the plan of completion and re-checking, i.e., the FI subject had better solving ability than the FD subject in the stage of planning the completion and re-checking. In contrast, at the other Polya stages, there were no differences.